Synthesis and electrochemical performance of graphene-TiO2-carbon paste nanocomposites electrode in phenol detection. (August 2019) - Nurdin, Muhammad; Agusu, La; Putra, Abdul Azis Marzuki; Maulidiyah, Maulidiyah; Arham, Zul; Wibowo, Dwiprayogo; Muzakkar, Muhammad Zakir; Umar, Akrajas Ali
Abstract: The addition of graphene (G) in to the TiO2 anatase-carbon paste (GTC) composite electrode has been found to effectively enhance its electrochemical sensing sensitivity towards phenol. In this study, we found that the GTC electrode, which was prepared using a mixture of graphene obtained from Hummer method, TiO2 from Degussa P25 and carbon paste, shows exceptionally high sensitivity towards the presence of phenol in electrolyte solution (H2 SO4 0.1 M). The presence of phenol is indicated by the appearance of oxidation peak (Epa ) at potential of 0.12 V. In the typical process, the new GTC electrode can effectively detect the phenol down to 3.6620 × 10 −5  μM. The electrode also exhibits excellent stability property with reproducibility relative standard deviation (%RSDR ) and predicted reproducibility standard deviation (%PRSDR ) recorded are as low as 1.33% and 2.83%, respectively. The response linearity can be obtained up to the phenol concentration of 10 −4  μM. Nevertheless, the GTC performance is a concentration dependent with the optimum electrode is the sample using graphene and TiO2 as low as 0.015 and 0.3 g, respectively. The preparation and the characterization of the new electrode will be discussed in the detail. Graphical abstract: Graphene-anatase TiO2 -carbon paste composite electrode shows high performance in electrochemical sensing of phenolic compound.Image 1 Highlights: Facile synthesis of graphene-TiO2-carbon paste (GTC) nanocomposite electrode is reported. The addition of graphene (G) in the TiO2 anatase-carbon paste (GTC) composite electrode has effectively enhanced the electrochemical sensing sensitivity of GTC to phenol. The GTC electrode exhibits excellent stability and reproducibility properties with %RSDR and %PRSDR as low as 1.33% and 2.83%, respectively.